EXPLORING THE LINK BETWEEN EDUCATIONAL BACKGROUND AND JOB PERFORMANCE OF MANAGEMENT ASSOCIATES IN THE FINANCIAL INDUSTRY - Bo Shiuan Huang (PEOPLE: International Journal of Social Sciences, 2026)
This study investigated the Management Associate (MA) program of a financial institution to examine whether academic background meaningfully predicted job performance. Although many organizations prefer recruiting master’s degree holders under the assumption of superior workplace performance, the actual linkage between educational attainment and performance outcomes remains uncertain. Using secondary data analysis, this study found no significant relationship between MA performance and demographic variables such as education level, overseas degrees, academic major, prior work experience, and industry-related experience. Semi-structured interviews with MA recruitment specialists and HR managers further revealed that academic credentials function only as an initial screening criterion. Instead, soft skills—including proactiveness, communication and presentation abilities, problem-solving and logical reasoning, creativity, teamwork, work engagement, and career planning—along with hard skills such as industry knowledge, language proficiency, and professional financial certifications, exert greater influenced on long-term performance. Given the limited predictive value of objective background data, we recommend incorporating situational assessments, such as group case discussions, and strengthening personality assessments related to proactiveness in the recruitment process. These measures may enhance the prediction of long-term performance and improve retention among newly hired MAs.